2005
DOI: 10.1021/jp051525m
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured, Gd-Doped Ceria Promoted by Pt or Pd:  Investigation of the Electronic and Surface Structures and Relations to Chemical Properties

Abstract: Nanostructured ceria doped with other rare earth elements is a good oxygen ion conductor, which gives rise to various catalytic applications such as the construction of membranes for syngas production by partial oxidation of methane. This article focuses on the Gd-doped cerium dioxides, which can be modified with Pt or Pd to enhance the reactivity of the lattice oxygen in interaction with methane. The aim of the work is the elucidation of correlations between the structural, electronic, and chemical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 49 publications
4
36
0
Order By: Relevance
“…A satellite peak centered at 967 eV in the XPS spectrum of PrO 2 has been reported as being exclusively related to the tetravalent state of Pr in the PrO 2 compound. 24,25 Unfortunately, this XPS satellite peak is overlapped with the oxygen Auger peak (OKLL), making its exact determination difficult.…”
Section: Resultsmentioning
confidence: 99%
“…A satellite peak centered at 967 eV in the XPS spectrum of PrO 2 has been reported as being exclusively related to the tetravalent state of Pr in the PrO 2 compound. 24,25 Unfortunately, this XPS satellite peak is overlapped with the oxygen Auger peak (OKLL), making its exact determination difficult.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, extensive studies on RE-doped CeO 2 have shown that fine microstructures and microstructural variations (as a function of doping level and sintering temperature) play a key role in their conductivities. [11][12][13] On the other hand, mechanical properties of electrolytes are also important when considering the necessarily long term service of SOFCs, which is susceptible to thermal stress and mechanical stress during the cell operation. Because of this, various mechanical properties have been investigated for RE-doped CeO 2 , such as elastic modulus, 14,15 hardness, 16,17 and fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
“…This allows us to assume that, in actual fact, the gadolinium content exceeds 50 at %. Since the dependence of the lattice parameter on the gadolinium content exhibits an approximately linear behavior [22], the true gadolinium content appears to be close to 60 at %, which corresponds to the initial gadolinium content in the system. Therefore, almost all Gd cations in the samples of the Ln-Mn system and in the low-temperature samples of the Gd-Mn-O system enter into the composition of the metastable solid solution based on ceria and the perovskite phase should be absent.…”
Section: X-ray Diffraction Analysismentioning
confidence: 95%
“…The maximum lattice parameter (5.448 Å) of the low-temperature fluorite phase in the Ce-Gd-Mn system is larger than the corresponding lattice parameter (5.435 Å) for the low-temperature (500°C) ceria sample that was prepared by the Pechini method and doped up to 50 at % Gd [22]. This allows us to assume that, in actual fact, the gadolinium content exceeds 50 at %.…”
Section: X-ray Diffraction Analysismentioning
confidence: 98%